Simulium hiroyukii, a new species of the subgenus Gomphostilbia (Diptera: Simuliidae) from Mount Murud, Sarawak, Malaysia - Ya'cob, Z.; Takaoka, Hiroyuki; Sofian-Azirun, Mohd (Magnolia Press, 2015)
Simulium (Gomphostilbia) hiroyukii is described based on females, males, pupae and larvae collected in Mount Murud, Sarawak, Malaysia. This new species is assigned to the Simulium darjeelingense species-group of the subgenus Gomphostilbia, and is characterized by the darkened fore coxae and the pupal gill with eight long filaments, of which middle and dorsal triplets have elongated primary and secondary stalks, respectively.